HUBUNGAN KEKERASAN DALAM BERPACARAN DENGAN RESILIENSI PADA MAHASISWA DI UNIVERSITAS X KOTA BEKASI - Afifah, Fauziah Vara; Merdiaty, Netty (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research explains the relationship between violence in dating and resilience in students at X University, Bekasi City, which is one of the private universities in Bekasi City. This research aims to determine whether there is a relationship between dating violence and resilience using 137 respondents from Universitas X. The method used in this research is quantitative correlational analysis with the aim of seeing the relationship between the two variables studied, in data analysis process using with helm of IBM SPSS 25 software. The results in this study show a correlation coefficient value of – p < 0,05. This value provides an explanation that violence in dating and resilience has a negative relationship. Based on research results which show that there is a relationship between violence in dating and resilience in students as University X.